Psychological Peculiarities of Organization of Parent-Child Relationships Among Older Preschoolers - Nataliia Semenova; Oleksandr Semenov; Nadiіa Alendar; Andrii Zdikhovskyi (Insight: the psychological dimensions of society, 2024)
The aim is to conduct theoretical-empirical research into the psychological content parameters of parent-child relationships in older preschool children. Methods. The research participants were parents and their children: n = 33 family triads: 18 families raising boys and 15 families raising girls, and n = 3 quadriads: two families having twins (a boy and a girl, and two girls), and one family having twin boys. The children were pupils of senior groups of preschool education institutions. The age of children ranged from 5 to 6 years. The sample of parents involved n = 72 individuals aged 19 to 37 years. Psycho-diagnostic instruments were used to find relevant psychological content parameters of parent-child relationships. Results. It was found that the verbal component of children’s relationships has one direct correlation with a favorable family situation and one inverse correlation with communication difficulties. The emotional component has one direct correlation with a favorable family situation and two inverse correlations with anxiety and family conflicts. It was established that the emotional component is a more dependent variable in comparison to the verbal component. It was highlighted that a favorable family situation has correlations with the verbal and emotional components of children. It was stated that, from the perspective of parents, emotional connection is the most loaded parameter which reflects the main dimensions of the atmosphere, upbringing traditions, and family values, and has all the significant correlations. It was found that optimal emotional contact on the part of parents contributes to the formation and growth of differentiated content features of interpersonal interaction in an adequate and congruent social situation. It was established that hyperactive concentration on a child demonstrates an internal position of parents in parent-child relationships. It was noted that this position manifests itself through leadership, control, discipline, and family rules used by parents. Discussion and сonclusions. It was substantiated that the development of parent-child relationships in the preschool age is determined by the differentiation of content features of interpersonal interaction in the educational subsystem “parents–children” and the type of behavior that is adequate and congruent with a social situation. It was generalized that family is a reference space of development that ensures the formation of behavioral patterns and the sphere of feelings and emotions. It was noted that children’s attempts to create interactions in the subsystem “parents–children” are important for building constructive parent-child relationships. It was recommended that the obtained results should be implemented in the theory and practice of teachers and psychologies of preschool education institutions.